Cost-effectiveness of TYRX absorbable antibacterial envelope for prevention of cardiovascular implantable electronic device infection. (4th March 2018) - Kay, Gemma; Eby, Elizabeth L.; Brown, Benedict; Lyon, Julie; Eggington, Simon; Kumar, Gayathri; Fenwick, Elisabeth; Sohail, M. Rizwan; Wright, David Jay
Abstract: Aims: Infection is a major complication of cardiovascular implantable electronic device (CIED) therapy that usually requires device extraction and is associated with increased morbidity and mortality. The TYRX Antibacterial Envelope is a polypropylene mesh that stabilizes the CIED and elutes minocycline and rifampin to reduce the risk of post-operative infection. Methods: A decision tree was developed to assess the cost-effectiveness of TYRX vs standard of care (SOC) following implantation of four CIED device types. The model was parameterized for a UK National Health Service perspective. Probabilities were derived from the literature. Resource use included drug acquisition and administration, hospitalization, adverse events, device extraction, and replacement. Incremental cost-effectiveness ratios (ICERs) were calculated from costs and quality-adjusted life-years (QALYs). Results: Over a 12-month time horizon, TYRX was less costly and more effective than SOC when utilized in patients with an ICD or CRT-D. TYRX was associated with ICERs of £46, 548 and £21, 768 per QALY gained in patients with an IPG or CRT-P, respectively. TYRX was cost-effective at a £30, 000 threshold at baseline probabilities of infection exceeding 1.65% (CRT-D), 1.95% (CRT-P), 1.87% (IPG), and 1.38% (ICD). Limitations and conclusions: Device-specific infection rates for high-risk patients were not available in the literature and not used in this analysis, potentially under-estimating the impact of TYRX in certain devices. Nevertheless, TYRX is associated with a reduction in post-operative infection risk relative to SOC, resulting in reduced healthcare resource utilization at an initial cost. The ICERs are below the accepted willingness-to-pay thresholds used by UK decision-makers. TYRX, therefore, represents a cost-effective prevention option for CIED patients at high-risk of post-operative infection.